2022
DOI: 10.3390/genes13071121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Angiotensin Converting Enzyme (ACE) I/D Polymorphism on Atherosclerotic Cardiovascular Disease and Cardiovascular Mortality Risk in Non-Hemodialyzed Chronic Kidney Disease: The Mediating Role of Plasma ACE Level

Abstract: The association between angiotensin-converting enzyme insertion/deletion (ACE I/D) polymorphisms and plasma ACE levels may allow for the optimization of a preventive intervention to reduce cardiovascular morbidity and mortality in the chronic kidney disease (CKD) population. In this study, we aimed to analyze the association between ACE I/D polymorphism and cardiovascular mortality risk among non-hemodialyzed chronic kidney disease patients. This cross-sectional study examined 70 patients of Javanese ethnic or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(74 reference statements)
0
4
1
Order By: Relevance
“…Other research, however, has not shown a correlation between circulating ACE activity and age (Miura et al, 1984;Soler et al, 2012;Yang et al, 2017). Aside from the evidence that ACE I/D polymorphism can directly affect higher ACE concentrations in plasma (Dai et al, 2019;Susilo et al, 2022), we surmise that the incongruences seen in this study may be attributable to the effect of RAAS inhibition on circulating ACE levels. In addition, different sample characteristics may potentially contribute to this discrepancy, as the majority of CKD patients in the present study have diabetes and hypertension.…”
Section: Discussioncontrasting
confidence: 64%
“…Other research, however, has not shown a correlation between circulating ACE activity and age (Miura et al, 1984;Soler et al, 2012;Yang et al, 2017). Aside from the evidence that ACE I/D polymorphism can directly affect higher ACE concentrations in plasma (Dai et al, 2019;Susilo et al, 2022), we surmise that the incongruences seen in this study may be attributable to the effect of RAAS inhibition on circulating ACE levels. In addition, different sample characteristics may potentially contribute to this discrepancy, as the majority of CKD patients in the present study have diabetes and hypertension.…”
Section: Discussioncontrasting
confidence: 64%
“…This was an observational analytical study with a cross-sectional design to analyze the role of IL-6 G174C gene polymorphism and IL-6 plasma levels with atherosclerotic cardiovascular disease and cardiovascular mortality risk scores in Javanese CKD patients. The study is a continuation of our previous study focusing on the effect of polymorphism in the ACE gene on atherosclerotic cardiovascular disease and cardiovascular mortality risk [ 31 ]. We have added several CKD patients to be included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were described in our previous paper [ 31 ]. Briefly, samples included in this study should fulfill the following inclusion criteria: (1) aged 40–79 years; (2) clinically stable CKD patients; and (3) Javanese ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we focused on the I/D polymorphism. The analysis of this polymorphism (the presence of the larger insertion (I) allele or the shorter deletion (D) allele) showed that the alleles are codominant and impact the levels of plasmatic ACE with homozygotes for the I allele having the lowest levels of the enzyme, heterozygous individuals having an intermediate level and homozygotes for the D allele having the highest levels [ 11 ].…”
Section: Introductionmentioning
confidence: 99%